Influence of downstream ramp on mass diffusion of various coaxial hydrogen and air injectors at supersonic combustion chamber. (15th December 2022) - Li, Z.; Abu-Hamdeh, Nidal H.; Musa, Awad; Zhang, Yuelei
Highlights: Effect of downstream ramp on the mixing of hydrogen transverse jet at supersonic flow is studied. The mixing performance of the coaxial fuel-air jets in various injector types is investigated. CFD method is used for the modeling of the cross jet injected from different injectors. Effects of ramp angle on fuel penetration and distribution is fully investigated. Abstract: The mixing efficiency of injection system inside combustion chamber of the scramjet significantly influence on the total performance of the hypersonic vehicles. In this study, the existence of the downstream ramp on the flow structure of hydrogen cross jet at supersonic air stream is comprehensively investigated. Computational fluid dynamic method is used to simulate flow structure of sonic hydrogen jet at supersonic air cross flow in existence of ramp positioned downstream of annular injectors. Effects of different annular injectors on mixing and penetration of fuel jet are also disclosed. Besides, effects of ramp angles on the distribution of hydrogen jet are also explored. Comparison of the 3-lobe injector in two different downstream angles of 10 and 30 deg indicates that the mixing efficiency increase about 30% when the angle of the downstream ramp is increased from 10 deg to 30 deg. Moreover, our results show that fuel mixing of the 3-lobe injector with ramp angle of 30 deg is about 55% more than circular jet at the same condition.